2012
DOI: 10.1099/jmm.0.032573-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal cephalosporinase in Enterobacter hormaechei as an ancestor of ACT-1 plasmid-mediated AmpC β-lactamase

Abstract: In this study of the diversity of AmpC b-lactamase in clinical isolates of Enterobacter spp., a strain was found carrying the plasmid-mediated AmpC b-lactamase ACT-1 gene on its chromosome. The strain was identified as Enterobacter hormaechei using phylogenetic analysis of 16S rRNA and hsp60 genes. In addition, the species was confirmed by DNA-DNA hybridization. The genetic environment of the bla ACT-1 gene was characterized, including the ampR and ampG genes, using a two-step PCR. The amino acid sequences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The AmpC β-lactamase is a member of the class C serine-dependent β-lactamase family. It was once a chromosomal enzyme of the Enterobacteriaceae but now is increasingly found as constitutively expressed from a plasmid [4, 5]. The proliferation of several different β-lactamases, each with the ability to confer resistance to both the cephalosporin and carbapenem β-lactam structures [6, 7], is foundational to the concern that an era of untreatable bacterial infection is nigh [8].…”
Section: Introductionmentioning
confidence: 99%
“…The AmpC β-lactamase is a member of the class C serine-dependent β-lactamase family. It was once a chromosomal enzyme of the Enterobacteriaceae but now is increasingly found as constitutively expressed from a plasmid [4, 5]. The proliferation of several different β-lactamases, each with the ability to confer resistance to both the cephalosporin and carbapenem β-lactam structures [6, 7], is foundational to the concern that an era of untreatable bacterial infection is nigh [8].…”
Section: Introductionmentioning
confidence: 99%
“…ESBLs and AmpC-type cephalo sporinases that can hydrolyze thirdgeneration cephalosporins such as cefotaxime or ceftazidime confer resistance more frequently to E. cloacae strains isolated in patients who previously received these antibiotics [29]. E. hormaechei is also an AmpC producer, and it has been recently demonstrated that the plasmid-mediated AmpC bla ACT-1 gene originated from the chromosome of E. hormaechei, which was previously believed to derive from E. cloacae [57].…”
Section: Antibiotic Resistance Of the E Cloacae Complexmentioning
confidence: 98%
“…In accordance with this observation, the use of cefepime increased the sensitivity of the DDST for the detection of ESBLs in Enterobacter from 16 to 61% when the disks were applied at the standard distance of 30 mm from clavulanate, and from 71 to 90% with closer application of the disks [61]. [14,16,63,64] VEB, GES/IBC, KPC E. cloacae [62,65,80,81,83,84,116] NMC-A, IMI-1, IMI-2 E. cloacae, Enterobacter asburiae [74][75][76][77][78][79]82] Ambler class B VIM E. cloacae, Enterobacter ludwigii [55,89,92] IMP, NDM-1 E. cloacae [86][87][88]90,91,96,97] Ambler class C Amp-C, ACT-1 E. cloacae, E. asburiae, E. hormaechei, Enterobacter kobei [57,113] Ambler class D OXA-48 E. cloacae [98,101] Fluoroquinolones Plasmid-mediated quinolone resistance Acetyltransferase AAC(6´)-Ib-cr E. cloacae [108,109,111,116] Qnr-mediated topoisom protection…”
Section: Antibiotic Resistance Of the E Cloacae Complexmentioning
confidence: 99%
“…Distinguishing β-lactamases in Enterobacterales has epidemiological significance. In this regard, some studies have demonstrated the contribution of Kluyvera, Citrobacter , and Enterobacter species to the recruitment and dissemination of plasmid-mediated extended-spectrum β-lactamases and/or AmpC β-lactamases [ 8 , [33] , [34] , [35] , [36] ]. Specifically, the presence of AmpC in plasmids has contributed to the rapid spread of this mechanism of resistance.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, knowing the distribution of ACT-type β-lactamases in Enterobacter species will allow inferences regarding the putative origin of pAmpCs that could emerge in clinically relevant pathogens. In this respect, the chromosomally encoded AmpC β-lactamase reported in E. hormaechei has been suggested as the putative progenitor of the pACT-1 found in Klebsiella pneumoniae [ 34 , 37 ].…”
Section: Resultsmentioning
confidence: 99%